2021
DOI: 10.3389/fpsyt.2021.736790
|View full text |Cite
|
Sign up to set email alerts
|

Does One Treatment Fit All? Effectiveness of a Multicomponent Cognitive Behavioral Therapy Program in Data-Driven Subtypes of Perinatal Depression

Abstract: Background: Current diagnostic systems of mental disorders are criticized for their poor validity and reliability, owing to the within disorder heterogeneity and between disorder homogeneity. The issue is important if treatments for mental disorders are to be tailored to individual needs. There is little information in this area on perinatal depression (PND), a highly prevalent condition globally.Aims: i) Quantify heterogeneity attributable to the polythetic diagnostic framework for PND and, ii) present eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…It also yielded a c-statistic of 0.75, which is in the range of 0.60 to 0.85 for models predicting depression onset, treatment outcome, and relapse [ 20 , 21 , 23 , 43 ]. Our findings build upon previous research where the concept of heterogeneity in depression has been leveraged to predict treatment outcomes accurately [ 29 ]. Besides accounting for heterogeneity in the clinical presentation for PND, this model also incorporates short and easy-to-measure constructs of sources of social support, relationship status and empowerment, and socioeconomic class.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…It also yielded a c-statistic of 0.75, which is in the range of 0.60 to 0.85 for models predicting depression onset, treatment outcome, and relapse [ 20 , 21 , 23 , 43 ]. Our findings build upon previous research where the concept of heterogeneity in depression has been leveraged to predict treatment outcomes accurately [ 29 ]. Besides accounting for heterogeneity in the clinical presentation for PND, this model also incorporates short and easy-to-measure constructs of sources of social support, relationship status and empowerment, and socioeconomic class.…”
Section: Discussionsupporting
confidence: 77%
“…In this context, previous research has shown that depressive disorders are highly heterogeneous, with varying clinical presentations [ 1 , 45 , 46 ]. Our previous work [ 29 ] noted that for PND, the symptoms of HDRS clustered together into 365 different combinations. Research on heterogeneity in PND and its link with maternal morbidity, child outcomes, and treatment considerations are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations